Anti-HBs levels among children and adolescents with complete immunization schedule against hepatitis B virus. A cross-sectional study in Blumenau, State of Santa Catarina, Brazil, 2007-2008 - Livramento,Andréa do (2011)
INTRODUCTION: Vaccination is the main tool for preventing hepatitis B virus (HBV) infection; however, following the completion of the vaccination series, the concentrations of anti-HBs can decline over the years and reach levels less than 10mIU/mL. The persistence of protection in these individuals is still unknown. The present study aimed to determine the anti-HBs antibody levels among children and adolescents who had received a complete vaccination course for hepatitis B. METHODS: Antibodies against HBV surface antigen (anti-HBs) were tested in 371 individuals aged 10 to 15 years-old. RESULTS: Volunteers who showed undetectable quantities of anti-HBs accounted for 10.2% of the population studied and 39.9% presented antibody titers of less than 10mIU/mL. Anti-HBs ≥ 10mIU/mL were verified in 49.9%. CONCLUSIONS: These results corroborate other studies indicating levels of anti-HBs below 10mIU/mL in vaccinated individuals. Additional studies are required to assess whether this indicates susceptibility to HBV infection and the need and age for booster doses.